Male × female interaction for a pre-copulatory trait, but not a post-copulatory trait, among cosmopolitan populations of Drosophila melanogaster. - Alison Pischedda; Andrew D Stewart; Monica K Little (PLoS ONE, 2012)
Sexual coevolution occurs when changes in the phenotype of one sex select for changes in the other sex. We can identify the "footprint" of this coevolution by mating males and females from different populations and testing for a male-female genotype interaction for a trait associated with male (or female) performance. Here we mated male Drosophila melanogaster from five different continents with females from their own and different continents to test for a male-female interaction for mating speed, a pre-copulatory trait, and female reproductive investment, a post-copulatory trait. We found a strong male-female interaction for mating speed, consistent with previous studies using different populations, suggesting that the potential for sexual coevolution for this trait is present in this species. In contrast, we did not detect a male-female interaction for female reproductive investment. Although a male-female interaction for mating speed is compatible with the hypothesis of ongoing sexual coevolution, the nature of our experimental design is unable to exclude alternate explanations. Thus, the evolutionary mechanisms promoting male-female genotype interactions for pre-copulatory mating traits in D. melanogaster warrant further investigation.